Genetic manipulation of bacteriophage T4 utilizing the CRISPR-Cas13b system - Bhoobalan-Chitty, Yuvaraj; Stouf, Mathieu; De Paepe, Marianne (Frontiers in Genome Editing, 2024)
CRISPR-Cas type II and type V systems are inefficient in modifying bacteriophage T4 genome, due to hypermodification of its DNA. Here, we present a genome editing technique for bacteriophage T4 using the type VI CRISPR-Cas system. Using BzCas13b targeting of T4 phage, we were able to individually delete both T4 glucosyl transferase genes, α-gt and β-gt. Furthermore, we employed this method to mutate two conserved residues within the T4 DNA polymerase and to introduce the yellow fluorescent protein (YFP) coding sequence into T4 phage genome, enabling us to visualize phage infections. This T4 genome editing protocol was optimized to generate recombinant phages within a 6-hour timescale. Finally, spacers homologous to a variety of T4 genes were used to study the generality of Cas13b targeting, revealing important variability in targeting efficiency. Overall, this method constitutes a rapid and effective means of generating specific T4 phage mutants, which could be extended to other T4-like phages.